Subtitling strategies of Singlish particles and their effects on foreign audiences' comprehension: Ah Boys to Men series as a case study - Chia, Li Fang (Nanyang Technological University, 2023)
Singlish particles (e.g., “lah”) are characteristic of Singlish, often carrying important pragmatic meanings. However, these particles are typically not reflected in the subtitles of local films. Through an analysis of the English and Chinese subtitles for dialogues containing Singlish particles in the Ah Boys to Men film series, it was found that “deletion”, “paraphrase”, “transliteration” and “transcription” were the common strategies used to subtitle Singlish particles. While most of the “deletions” did not result in a change or loss in meaning, there was a proportion of the subtitles which did not convey their implied meanings. Hence, a self-administered online survey was conducted with eighty-two foreign respondents to investigate whether current subtitling strategies affected their comprehension of the particles. The survey found that most of the participants were able to accurately interpret their implied meanings and were reported to have relied mostly on the speaker’s tone, body language and facial expressions as cues. However, there were also some respondents who had interpretations that were completely different from what was intended. Approximately half of the respondents also either remained neutral or had found the comprehension process difficult and felt that it was important for subtitles to convey the nuances of Singlish particles. Hence, this paper calls for more scrutiny on how Singlish particles are subtitled and for subtitlers to pay greater attention to the aforementioned visual and verbal modes (i.e., speaker’s tone, facial expressions and body language) when translating Singlish particles as they can complement the subtitles in conveying their complex meanings.